Kecenderungan Terhadap Pemilihan Kerjaya Keusahawanan Mengikut Persepsi Peserta Skim Usahawan Siswa. (Sains Humanika, 2011)
Entrepreneurship field offers a wide range of career opportunities, yet, it is unpopular among Malaysian graduates. Many put this field in second or even third priority as their career choice, due to lack of awareness related to the potential of this field. This study was conducted to identify the perception of Malaysian graduates toward career in entrepreneurship field. Survey method was used using questionnaires from a sample of 266 participants of Graduate Entrepreneurship Scheme through random stratified sampling technique. In additioninterviews were also conducted with six participants that were chosen by using snowball technique. The finding of this study showed that the participants of Graduate Entrepreneurship Scheme have positive perception towards career in entrepreneurship field. This is due to the exposure they hadthrough entrepreneurship training. The finding gave reflection that entrepreneurship education can change individual’s perception towards having a career in entrepreneurship field.
Keywords: Entrepreneurship education; graduate entrepreneurship scheme; tendency; graduate; career